Pengaruh pengetahuan perpajakan, sanksi perpajakan dan kesadaran wajib pajak terhadap kepatuhan wajib pajak dalam membayar Pajak Bumi dan Bangunan (PBB) di Kota Samarinda - Kristianus Silaban, Yoas; Iwan Kesuma , Agus (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
This study aims to examine the effect of taxation knowledge, tax sanctions, and taxpayer awareness on taxpayer compliance in paying Land and Building Tax in Samarinda City. This type of research is quantitative research with primary data sources. As for sample determination, researchers used the simple random sampling method. Samples were collected through distributing questionnaires with Likert scale measurements. The analysis techniques used are validity test, reliability test, classical assumption test (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis and hypothesis testing (t statistical test and coefficient of determination analysis). The results showed that tax knowledge, tax sanctions, and taxpayer awareness had a positive and significant effect on taxpayer compliance in paying Land and Building Tax in Samarinda City.